The Effectiveness of Sea Urchin Extract (Echinometra matthaei) for Wound Healing on Deep Second-Degree in White Rats (Rattus norvegicus) Wistar - Angelica Kresnamurti; Dita Nurlita R; Fitri Budiarti (Journal of Tropical Pharmacy and Chemistry, 2021)
Background: Burns is a form of tissue damage caused by high temperatures. Echinometra matthaei sea urchins have several secondary metabolites that can potentially help in the healing process of burns. In this study, 70% E. matthaei ethanol extract was formulated in the form of O / W (oil in water) type cream preparations which were applied topically. Objective: This study aims to determine the effectiveness of E. matthaei ethanol extract cream preparations on the healing of second-degree burns in Wistar strain rats. In this study preparations were made in 3 formulations, namely Formulation 1 (extract concentration of 1%), Formulation 2 (extract concentration of 3%), and Formulation 3 (extract concentration of 5%). This research was conducted for 7 days with the method used is the post-test only control group design. Experiments were given induction of burns using a hot plate with a diameter of 20 mm at a temperature of ± 200ºC for 15 seconds. Wound healing is observed periodically by observing macroscopically healing inflammation of the inflammatory phase and observing tissue growth in the proliferation phase. Results: The average percentage of inflammation healing showed improvement in the F2: 100%, F1: 80%, F3: 71% results were better than the wound group: 50% as evidenced by the value ? = 0.012 (